Da noção de verdade ao realismo: Tarski abriu o universo de Popper? - Diogo, Vitor Leite Primo (2015)
Popper became known as great critic of positivism and disseminate the theoretical advances of fallibilism. This research builds upon this commonplace intending to answer the following questions: What is the role of Tarski's influence in the formulation of the notion of truth in Popper? Which are the consequences? On the first two chapters we will describe at what times of the first edition of the scientific research of Logic Popper debates issues that connect with the notion of truth in an indirect way, being the first chapter the critical part and the second to develop a way to positivist assumptions. The third chapter will deal with Tarski´s semantic notion of truth. We will present what was his goal and to what extent could he realize it. In the fourth and final chapter, we will present the way in which the truth as correspondence with the facts is possible. The scenario for the argumentation is made by Popper's realism. Thus, describing the development of the notion of truth in Popper, we will seek to maintain that his epistemology was corrected and expanded in debate with other thoughts. And the notion of reality depends, strongly, from the theoretical framework.